(untitled) (Health Renaissance, 2011)
Introduction: Homicide means killing of one human being as a result of conduct of another human being. This study of medico-legal and epidemiological details of homicidal cases would help in enhancement of various stakeholders in law enforcing agencies with the view to benefit the process of scientific crime detection and proper administration of justice at large. Objective: To identify the various medico-legal and epidemiological factors involved in homicide. Materials and method: A prospective cross-sectional study was conducted in fatal homicide victims brought for medico-legal autopsy in BPKIHS, during the period of 15th April 2009 to 14th July 2010.Data were collected using pre tested questionnaire by direct interview to the visitors of victim, information from the police record along with postmortem examination of the victim. Results: Out of the total 50 cases, the ratio of male to female victim was 4:1. More than half of the victims were of age 21-40 years (52%). More of the homicide victims were of rural areas (56%) and illiterate (32%). Injuries by sharp weapon were most common cause of death (36%) very closely followed by firearm injuries (34%). Most of the victim remained totally deprived of any medical help (60%). Conclusion: The homicide victims in eastern Nepal constituted illiterate adult male from rural area a dominant group. Sharp weapons were commonly employed in this region for homicide. Fatality of the victim can be highly minimized if medical and surgical interventions are be promptly prearranged. Proper counselling for developing positive attitude and controlling the aggression in youth have to be Promoted at large by the government. Keywords: Homicide; Medico-legal; sharp weapon injury; firearm injury DOI: 10.3126/hren.v9i1.4356 Health Renaissance, 2011: Vol.9 No.1:15-19